Role of the ocular surface microbiome in allergic disease. Issue 5 (October 2019) - Cavuoto, Kara M.; Stradiotto, Allison C.; Galor, Anat
Abstract : Purpose of review: The purpose of this review is to provide an update regarding new and emerging data on the role of the ocular surface microbiome in allergic disease. Recent findings: Recent findings support the role of the microbiome in the pathophysiology of allergic disease of the ocular surface. Summary: Understanding the role of the ocular surface microbiome in allergic disease may provide a new target for the development of therapeutic interventions.